Pengaruh Kepemilikan Institusional, Risiko Keuangan, Nilai Perusahaan, Dan Ukuran Perusahaan Terhadap Perataan Laba - Muh Afilza Prasetya; Heru Suwasono (Riset Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of institutional ownership, financial risk, firm value, and firm size on income smoothing in the healthcare and industrial sectors in Indonesia during 2020-2024. The research sample consisted of 38 companies from 18 companies in the healthcare sector and 65 companies from 41 companies in the industrial sector, selected through purposive sampling from the population of companies listed on the Indonesia Stock Exchange during 2020-2024. This study uses quantitative data analyzed using multiple linear regression methods to examine the effect of institutional ownership, financial risk, firm value, and firm size on income smoothing. The results indicate that institutional ownership and financial risk have no effect on income smoothing. Firm value has a positive effect on income smoothing, while firm size has a negative effect on income smoothing.